Sodium Hydroxide Treatment for Cellulose Fiber Accessibility from Corncobs under Microwave Assistive - Hanif, Muhammad; Krisanti, Aknasasia Virginia; Salfitri, Selvy; Darni, Yuli; Utami, Herti; Azwar, Edwin; Gunawan, Poernomo (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
Corncob is abundantly available lignocellulosic biomass resources obtained from crops harvesting and found to be solid waste accumulation on a field. Less corncob is used as a solid fuel for cooking, and a more significant portion is vanished on the field by burning. Promisingly, corncob contains considerable cellulose as one value-added component potentially utilized as biomaterial or biofuel feedstock. However, the presence of lignin in natural lignocellulosic biomass results in recalcitrant structure and hinders cellulose accessibility. This study aimed to investigate microwave-assisted alkaline treatment to retain cellulose in the solid product while removing other impurities in corncob, especially hemicellulose and lignin. Sodium hydroxide was selected as a chemical with some variations in concentration. The chemical treatment was carried out under 400 W microwave power with various residence times and a 1:10 solid to liquor ratio. The cellulose content upgraded from 26.97% to 71.26% while reducing hemicellulose and lignin from 38.49% to 18.15% and 19.28% to 6.4%, respectively, on chemical treatment using 8% sodium hydroxide concentration for 20 minutes residence time. Scanning electron microscope (SEM) and Fourier transform infrared (FTIR) analysis also confirmed the results. The treated corncob also increased its crystallinity from 30.11% to 52.91%.